Changes of gonadotropin receptors and Ras subfamily genes during maturation in porcine cumulus cells - Yuna Nam; Hee-Tae Cheong; Sang-Hee Lee (Journal of Animal Reproduction and Biotechnology)
Background: The cumulus cells (CC) play an essential role in protecting oocytes and providing molecular signals for meiotic and cytoplasmic maturation. Gonadotropins stimulate CC proliferation, promote the release of factors that resume oocyte maturation, and activate small G proteins. Among these, Ras, a GTP-binding protein, participates in signaling pathways that regulate cell growth, division, and proliferation. This study aimed to investigate the changes in the Ras subfamily and gonadotropin receptor expression during porcine CC maturation. Methods: Cumulus-oocyte complexes (COCs) were incubated in a medium supplemented with follicular stimulating hormone (FSH), luteinizing hormone (LH), and epidermal growth factor (EGF) for 44 hours. CCs were collected from the COCs at 0, 22, and 44 hours, and mRNA expression levels of gonadotropin and growth factor receptors (FSHR, LHR, EGFR), Ras subfamily members (H-Ras, K-Ras, N-Ras, R-Ras), and Ras GTPases (RASA1, SOS1) were analyzed using quantitative RT-PCR. Results: The results revealed that LHR and R-Ras mRNA expression significantly increased only at 44 hours compared to the 0-hour group (p < 0.05). Conversely, RASA1 mRNA levels decreased significantly at the same time points. No significant changes were observed in H-Ras, K-Ras, N-Ras, or SOS1 expression. Conclusions: In conclusion, the observed increase in LHR and R-Ras and the decrease in RASA1 provide new insights into the molecular dynamics of Ras subfamily members during porcine CC maturation, contributing to a better understanding of the regulatory mechanisms underlying oocyte development.